Sustainability Analysis Of The Round Coconut Business System In Indragiri Hilir Using A Multi-Stakeholder Approach - Ismawati, Ike; Purnama, Indra; Apriyanto, Mulono (LPPM Universitas PGRI Sumatera Barat, 2024)
This study aims to analyze the sustainability level of the coconut farming system in Indragiri Hilir Regency using a multistakeholder approach and the SAFA (Sustainability Assessment of Food and Agriculture Systems) framework. The analysis covers four sustainability dimensions: economic, environmental, social, and governance. Data were collected through Likert-scale questionnaires, interviews, and focus group discussions (FGDs) involving various stakeholders such as farmers, traders, cooperatives, village governments, and related government agencies. The results show that the social dimension has the highest sustainability score (4.26; categorized as